Relationship of Biochemical and Sonographic Markers with Disease Severity in Rosacea Patients Without Cardiovascular Disease - Banu Ismail Mendi; Bokebatur Ahmet Rasit Mendi; Banu Farabi; Mehmet Fatih Atak (Life)
Rosacea is a chronic inflammatory skin disorder characterized by central facial redness, papulopustular lesions, and occasionally phymatous changes. There is ongoing debate regarding rosacea as a cutaneous disease with systemic inflammatory effects and its associations with cardiovascular diseases. Although the pathogenesis of both atherosclerosis and rosacea demonstrate notable similarities, particularly in the central role of inflammation, significant gaps in understanding these connections remain. This study aims to investigate this potential relationship by assessing biochemical markers and sonographic findings in rosacea patients who were divided into groups based on disease severity. Our study included 73 rosacea patients and 73 age- and sex-matched controls, without cardiovascular disease. Demographic, clinical, and laboratory data were recorded for all participants. Carotid intima–media thickness and the thickness of subcutaneous, preperitoneal, posterior perirenal, and aortic-level visceral adipose tissues were measured by ultrasonography. The erythrocyte sedimentation rate was significantly elevated in rosacea patients versus controls. Additionally, sonographic assessments revealed that both aortic-level visceral adipose tissue and preperitoneal adipose tissue were significantly thicker in rosacea patients than in the control group, a finding corroborated by multivariable linear regression analysis. While thicker preperitoneal and perirenal adipose tissues were observed with increasing disease severity, these differences did not achieve statistical significance when subjected to multivariable linear regression analysis. The thorough examination and follow-up of patients with rosacea for cardiovascular risk factors may be necessary in clinical practice.